ANALISIS AKUNTABILITAS, TRANSPARANSI, DAN KETEPATAN WAKTU TERHADAP KINERJA ANGGARAN DENGAN KONSEP VALUE FOR MONEY (Studi Kasus pada Rumah Sakit Umum Daerah Rantauprapat) - Fathan Aulia Siregar; Haryanto Haryanto (Diponegoro Journal of Accounting, 2026)
This study aims to examine the influence of accountability, transparency, and timeliness on value for money-based budget performance at Rantauprapat Regional General Hospital (RSUD Rantauprapat). Using a quantitative approach, this study involved 42 employees from the finance and planning divisions as participants through a saturated sampling technique. A questionnaire instrument was used to collect primary data, which was then analyzed using multiple linear regression after passing the stages of validity testing, reliability testing, and classical assumption checks. This study is grounded in stewardship theory, which positions hospital management as stewards responsible for managing public funds for the benefit of society. The findings prove that accountability, transparency, and timeliness, both individually (partially) and simultaneously, have a significant positive impact on the budget performance of RSUD Rantauprapat within the value for money framework. This confirms that strengthening the accountability system, transparency of budget data, and disciplined adherence to reporting deadlines will encourage the creation of more economical, efficient, and effective hospital financial management. This research is expected to enrich the literature on public sector accounting while serving as strategic input for the board of directors of RSUD and local governments in optimizing financial governance and minimizing potential budget leakages.